PENGGUNAAN MEDIA KALENDER KATA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA DOWN SYNDROME KELAS IV SKH DIAN BAHAGIA KABUPATEN TANGERANG BANTEN - Iif Fauziah; Dr. Joko Yuwono, M.Pd; Dedi Mulia, M.Pd (Jurusan Pendidikan Luar Biasa, FKIP Universitas Sultan Ageng Tirtayasa, 2018)
Abstract This study aims to find out and describe the implementation of early learning reading media by using word calendar media in class IV SKh Dian Bahagia Tigaraksa Tangerang Regency. This research is a quantitative study using the Single Subject Research (SSR) approach. The research subjects were one class IV down syndrome student at Dian Bahagia Tigaraksa District, Tangerang Regency. This research was conducted using the A-B-A design. Data retrieval is carried out using the initial reading ability test. Data analysis used is descriptive statistical analysis. The analysis phase includes analysis in conditions and analysis between conditions. The results showed that word calendar media showed an increase in the ability to read the beginning. This is indicated by overlapping data (Overlap) in the analysis between A1 / B and B / A2 conditions of 0%, which means that the small percentage overlap shows the greater influence on the target behavior. This is also supported by the increase in the score of the initial word reading ability obtained by the subjects during the baseline phase 1 (A1), intervention phase (B) and baseline phase 2 (A2). In the baseline phase 1 (A1) the average score of the subjects was 66.67%. In the intervention phase the average score was 93.33%. At baseline phase 2 (A2) the average subject scores 83.33%.